WIRELESS SENSOR NETWORK INTEGRATION WITH FREQUENCY CONVERTER BY USING MULTI-HOP PROTOCOL - Linh, Le Manh (My University, 2015)
The area of wireless sensor network is rapidly growing and a corresponding growth in the demand of its applications. The need to collect data from remote positions is in fact unavoidable. Since the reliable communication distance in WSNs is relatively short, a multi-hop communication must be applied to be able to cover larger areas. A generic, modular and stackable WSN node, named UWASA Node has been developed by the University of Vaasa and Aalto University. Besides, the UWASA Node has been interfaced to Vacon Frequency Converter to be able to collect the frequency converter data in a wireless manner. A multi-hop communication will remarkably increase the coverage of the WSN, which is used to collect the frequency converter data. In this thesis, a multi-hop protocol for collecting data from frequency converter is implemented to UWASA Nodes. Firstly, an overview of IEEE 802.15.4 architecture and routing protocols are introduced. Then the basic of WSN platform of the UWASA Node is discussed. Finally, a design and implementation of multi-hop protocol is explained in detail, and several experiments are performed to verify the system performance under the protocol. Developed protocol provides a solution to collect data and control remote devices.
Keywords: fi=Communications and System Engineering|en=Communications and System Engineering|; fi=Master's Degree Programme in Telecommunication Engineering|en=Master's Degree Programme in Telecommunication Engineering|